Posttranslational Modifications of GLUT4 Affect Its Subcellular Localization and Translocation - Sadler, Jessica B. A. (Molecular Diversity Preservation International (MDPI), 2013)
The facilitative glucose transporter type 4 (GLUT4) is expressed in adipose and muscle and plays a vital role in whole body glucose homeostasis. In the absence of insulin, only ~1% of cellular GLUT4 is present at the plasma membrane, with the vast majority localizing to intracellular organelles. GLUT4 is retained intracellularly by continuous trafficking through two inter-related cycles. GLUT4 passes through recycling endosomes, the trans Golgi network and an insulin-sensitive intracellular compartment, termed GLUT4-storage vesicles or GSVs. It is from GSVs that GLUT4 is mobilized to the cell surface in response to insulin, where it increases the rate of glucose uptake into the cell. As with many physiological responses to external stimuli, this regulated trafficking event involves multiple posttranslational modifications. This review outlines the roles of posttranslational modifications of GLUT4 on its function and insulin-regulated trafficking.